Does Greening of Supply Chain, Corporate Sustainability and Efficiency of Social and Economic Corporate Strategies Matter for Corporate Financial Performance? - Sriparinya Toopgajank; Chonticha Somjai; Chandej Charoenwiriyakul; Kulnaree Maneechote (International Journal of Supply Chain Management, 2019)
The main purpose of the study is to examine the impact of greening of supply chain, corporate sustainability and efficiency of social and economic corporate strategies on the corporate financial performance of Thai manufacturing firms. Firstly, the study has examined the direct impact of the social and economic efficiency strategies on the corporate financial performance, secondly, the mediating role of corporate social performance, corporate environmental performance and the green supply chain in the relationship between corporate efficacy strategies and the corporate financial performance is examined. The study has surveyed the 435 Thai mangers and used the SEM-PLS to analyze the data. The findings of the study indicate the fact that the company incorporates environmental and social issues voluntarily in its business operations. Therefore, it is difficult to adopt sustainable business strategies. Sustainable strategies implementation is different in the organization in contrast to other business strategies. There is a clear relation between the profit and products for achieve operational goals. The focus in sustainability is to achieve financial, environmental, and social performance respectively. Managers are supported with the achievement of environmental, social and financial goals altogether.